Major complications of caudal block: A prospective survey of 973 cases in adult anorectal surgery - Liwei Xie; Honglei Tao; Fangping Bao; Yeke Zhu; Fuquan Fang; Xiuxia Bao; Shengmei Zhu; Xianhui Kang (Heliyon, 2023)
Background: We conducted a prospective study of surgical inpatients at a teaching hospital to assess the incidence and potential risk factors for major complications of caudal anesthesia in anorectal surgery. Methods: A total of 973 patients undergoing anorectal surgery under caudal block were included in this prospective, observer-blinded trial after providing consent. Demographic information, detailed perioperative information, anesthesia-related complications and postoperative follow-up information were recorded. Meanwhile, the incidence and risk factors for major caudal anesthesia-related complications were analyzed. Results: A total of 973 patients underwent caudal block. The effective rate was 95.38 % (928 cases). However, there were still 38 (3.91 %) cases with insufficient block and 7 (0.72 %) cases with no block. The major anesthesia-related complications were local anesthetic systemic toxicity (9, 0.92 %), cauda equine syndrome (1, 0.10 %), transient neurological symptoms (3, 0.31 %) and localized pain at the caudal insertion site (30, 3.08 %). The identified risk factor for local anesthetic systemic toxicity was multiple attempts locating the caudal space (OR = 5.30; 1.21–23.29). The identified risk factor for localized pain at the caudal insertion site was multiple attempts locating the caudal space (OR = 10.57; 4.89–22.86). Conclusion: The main complications of caudal block in adult patients are transient neurological symptoms, cauda equine syndrome, serious local anesthetic systemic toxicity and localized pain at the caudal insertion site. Overall, the incidence of complications is low and symptoms are mild. Caudal block is still a safe and reliable method for anesthesia in adult anorectal surgery.